O “José de Arimatéia” da tradição arturiana - Antônio L. Furtado (Filologia e Linguística Portuguesa, 2001)
An enigma in a text of the XIIIth century is investigated through the study of sources, as well as historic and linguistic considerations. The work under scrutiny belongs to the Matter of Britain, significantly represented in medieval Portuguese literature.